The Effect of Return On Assets, Current Ratio, Debt To Equity Ratio on Income Growth in Automotive Companies Registered in Indonesia Stock Exchange - Euodia Stefani Handiyanti (Yayasan Ahmar Cendekia Indonesia, 2020)
This study aims to examine and prove the effect of return on assets, current ratio, debt to equity ratio partially or simultaneously on profit growth in automotive companies listed on the Indonesia Stock Exchange. The data source used in this study is secondary data, which takes and quotes from financial reports obtained on the official website of the Indonesia Stock Exchange and financial reports on the official websites of each company. The sample selection used purposive sampling methodand obtained a number of 45 automotive companies. The analysis technique used in this research is the classical assumption test and multiple regression analysis. The data in this study were processed using the SPSS version 25 program. The partial test results (t test) show that the Return on Assets and Debt to Equity Ratio have a significant effect on profit growth in automotive companies listed on the Indonesia Stock Exchange for the period 2014-2018. Meanwhile, the Current Ratio has no significant effect on profit growth in automotive companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Simultaneous test results (Test F) show that the variables return on assets, current ratio, debt to equity ratio together have a significant effect on profit growth in automotive companies listed on the Indonesia Stock Exchange for the period 2014-2018.